Occupational therapy in Australian acute hospitals: A modified practice - Britton, L.; Rosenwax, Lorna; McNamara, Beverley (Wiley-Blackwell Publishing Asia, 2016)
© 2016. Background/aim: Ongoing changes to health-care funding Australia wide continue to influence how occupational therapists practise in acute hospitals. This study describes the practice challenges experienced by Western Australian acute care occupational therapists. Then, it explores if and how acute care occupational therapists are modifying their practice in response to these practice changes. Methodology: This study used a qualitative grounded theory approach. Semi-structured interviews were completed with 13 purposively selected acute care occupational therapists from four Western Australian metropolitan hospitals. Data were analysed using a constant comparative method to provide detailed descriptions of acute care occupational therapy practice and to generate theory. Findings: Five conceptual categories were developed. The first two addressed practice challenges: pragmatic organisational influences on client care and establishing a professional identity within the multidisciplinary team. Three categories related to therapist responses are as follows: becoming the client advocate, being the facilitator and applying clinical reasoning. Finally, modified practice was identified as the core category which explains the process whereby acute care occupational therapists are ensuring they remain relevant and authentic in the acute care context. Conclusion: Western Australian acute care occupational therapists are practising in a highly complex health context that presents many challenges. They are responding by using a modified form of practice that ensures occupational therapy skills remain relevant within the narrow confines of this health setting.